RETRACTED ARTICLE: Pancreatic cancer-initiating cell exosome message transfer into noncancer-initiating cells: the importance of CD44v6 in reprogramming - Wang, Zhe; Sun, Hanxue; Provaznik, Jan; Hackert, Thilo; Zöller, Margot (Journal of experimental & clinical cancer research, 2019)
Background: Cancer-initiating cell (CIC) exosomes (CIC-TEX) are suggested reprogramming Non-CIC. Mode of message transfer and engagement of CIC-markers being disputed, we elaborated the impact of CD44v6 and Tspan8 on the response of Non-CIC. Methods: Non-metastasizing CD44v6- and Tspan8-knockdown (kd) pancreatic cancer cells served as Non-CIC. CIC-TEX coculture-induced changes were evaluated by deep-sequencing and functional assays. Tumor progression was surveyed during in vivo CIC-TEX treatment. Results: Deep-sequencing of CIC-TEX-cocultured CD44v6kd-Non-CIC revealed pronounced mRNA changes in signaling, transport, transcription and translation; altered miRNA affected metabolism, signaling and transcription. CIC-TEX coculture-induced changes in Tspan8kd-Non-CIC mostly relied on CIC-TEX-Tspan8 being required for targeting. CIC-TEX transfer supported apoptosis resistance and significantly promoted epithelial mesenchymal transition, migration, invasion and (lymph)angiogenesis of the kd Non-CIC in vitro and in vivo, deep-sequencing allowing individual mRNA and miRNA assignment to altered functions. Importantly, CIC-TEX act as a hub, initiated by CD44v6-dependent RTK, GPCR and integrin activation and involving CD44v6-assisted transcription and RNA processing. Accordingly, a kinase inhibitor hampered CIC-TEX-fostered tumor progression, which was backed by an anti-Tspan8 blockade of CIC-TEX binding. Conclusions: This in depth report on the in vitro and in vivo impact of CIC-TEX on CD44v6kd and Tspan8kd Non-CIC unravels hub CIC-TEX activity, highlighting a prominent contribution of the CIC-markers CD44v6 to signaling cascade activation, transcription, translation and miRNA processing in Non-CIC and of Tspan8 to CIC-TEX targeting. Blocking CIC-TEX binding/uptake and uptake-initiated target cell activation significantly mitigated the deleterious CIC-TEX impact on CD44v6kd and Tspan8kd Non-CIC.
Gesehen am 18.06.2019